Multimorbidity patterns in dementia and mild cognitive impairment - Valdevila Figueira, José Alejandro; Valdevila Santiesteban, Rocío; Carvajal Parra, Indira Dayana; Benenaula Vargas, Luis Patricio; Ramírez, Andrés; Leon-Rojas, Jose E.; Rodas, Jose A. (Frontiers in Psychiatry, 2024)
DesignThis is a retrospective cohort study. Setting: The study was conducted at the Instituto de Neurociencias de la Junta de Beneficencia de Guayaquil, a primary neuroscience institute in Ecuador.ParticipantsThe study evaluated 425 participants diagnosed with Mild Cognitive Impairment (MCI) or dementia, out of which 272 individuals (mean age = 75 years; 164 female) presenting specific medical conditions were selected for analysis.MeasurementsData were collected on demographics, medical history, and neuropsychological assessment using the Neuropsi scale. Conditions such as Type 2 Diabetes Mellitus, hypertension, obesity, and history of traumatic brain injury were specifically noted.ResultsLatent Class Analysis identified three distinct classes of patients: Unspecified Cognitive Deterioration, Dementia, and MCI. The three-class model provided the best fit, revealing varied morbidity patterns and highlighting the influence of vascular and metabolic conditions on cognitive decline. Notably, similarities in hypertension and diabetes prevalence between Dementia and MCI classes suggested shared risk factors. The study also found no significant age differences between the classes, indicating that age alone might not be the primary determinant in the progression of cognitive decline.ConclusionsThe study underscores the complexity of dementia and MCI in an ageing Ecuadorian population, with vascular health playing a crucial role in cognitive impairment. These findings advocate for a holistic approach in managing dementia and MCI, emphasising the importance of addressing cardiovascular and metabolic health alongside neurocognitive care. The distinct morbidity patterns identified offer insights into tailored intervention strategies, highlighting the need for comprehensive, multidisciplinary care in dementia management.